EVALUASI TATA LETAK FASILITAS PRODUKSI KRIPIK PISANG PADA CAHAYA INDI KABUPATEN DONGGALA - Tubagus, Pria (Fakultas Ekonomi Universitas Tadulako, 2017)
Basically, the purpose of production management is directed to create production efficiency and effectiveness to improve the results and contribute to the maximum profit achievement of the company. One of the problems in production management that influences the efficiency and effectiveness of production is layout arrangement of production facilities. This research is conducted through direct observation in Banana Chips Company ?Cahaya Indi? located in Donggala District. The type of research is quantitative using line balancing method and travel chart. The result of the line balancing method shows the efficiency of banana chips production process is 90,73% with idle time of 9,27%. While the result of travel chart method indicates a new layout design of banana chips production facility at Cahaya Indi is more effective with material flow load of 198,83 from the initial layout of 259,93